Isolamento e seleção de micro-organismos resistentes e capazes de volatilizar mercúrio - Patricia Giovanella (Química Nova, 2011)
Mercury (Hg) occurs in the environment as a natural and anthropogenic element, and through the years the accumulation of mercury has affected the integrity of ecosystems and human health. This study presents a screening of microorganisms resistant to organic and inorganic mercury, the determination of the minimum inhibitory concentration of Hg, the estimation of the mercury volatilization by selected microorganisms and the dynamics of volatilization. Eight Gram-negative bacteria resistant to high concentrations of mercury (60 to 210 mg L-1) were selected, and these isolates showed ability to volatilize the metal. The dynamics of the volatilization of the Proteus mirabilis M50C demonstrated that in only 4 h of incubation it was possible to volatilize 72% of the mercury present in the culture. The results showed promising application for bioremediation strategies.